The epistemic representation: visual production and communication of scientific knowledge. - Francisco López Cantos (Multidisciplinary Journal for Education, Social and Technological Sciences)
Despite its great influence on the History of Science, visual representations have attracted marginal interest until very recently and have often been regarded as a simple aid for mere illustration or scientific demonstration. However, it has been shown that visualization is an integral element of reasoning and a highly effective and common heuristic strategy in the scientific community and that the study of the conditions of visual production and communication are essential in the development of scientific knowledge.